PENGARUH MEKANISME CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS TERHADAP INTEGRITAS LAPORAN - Fellicia Monica Herada; Patricia Febrina Dwijayanti (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2022)
This study aims to examine and analyze the effect of corporate governance mechanism (managerial ownership, institutional ownership, independent commissioners and audit committees) and financial distress on the integrity of financial statements. The design of this research is quantitative research with hypothesis testing. The type of data used is quantitative data in the form of annual reports of manufacturing companies listed on the IDX for the 2018-2020 period as well as stock price data. The sampling technique used in this research is purposive sampling technique and the data analysis technique used is multiple linear regression. The results of this study indicate that the corporate governance mechanism variables (managerial ownership, institutional ownership, independent commissioners and audit committees) have no effect on the integrity of financial statements, while the financial distress variable has a negative effect on the integrity of financial statements.